Fenotipik varietas kedelai pada jarak tanam berbeda yang ditumpangsarikan dengan tanaman jagung - Suyamto Suyamto; Gatut Wahyu Anggoro Susanto; Pratanti Haksiwi Putri (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
The dual system planting aims to utilize existing resources so that they can be more efficient. The research design used separate plots repeated three times. The main plot consisted of soybean spacing of 40 cm x 10 cm (1 plant per hole) (JT-1), 40 cm x 15 cm (2 plants per hole) (JT-2) and 40 cm x 20 cm (2 plants per hole). Lubang) (JT-3), a subplot consisting of 11 varieties of soybeans. Soybeans were planted in 3 rows along 5 m which were intercropped with maize varieties Lamuru (120-50 cm) x 20 cm, (1 plant/hole) at IP2TP Muneng, Probolinggo Regency, East Java in MK II 2018. The results showed that the varieties